1984
DOI: 10.1163/22941932-90000413
|View full text |Cite
|
Sign up to set email alerts
|

The Annual Rhythm of Activity of the Lateral Meristems (Cambium and Phellogen) in Pinus Halepensis Mill. and Pinus Pinea L.

Abstract: The annual rhythms of cambial and phellogen activity in Pinus halepensis and P pinea were investigated. Under natural conditions the cambium of P halepensis begins its activity in autumn, enters a quiescent period during midwinter, resurnes activity towards spring and enters a second rest period in summer. The ring border is formed during summer. Irrigated plants growing outdoors were active almost all the year round.The cambium of P pinea is active between April and November and enters a true winter dormancy.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
48
0
1

Year Published

1987
1987
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(63 citation statements)
references
References 4 publications
3
48
0
1
Order By: Relevance
“…From a physiological viewpoint, P. pinea is known to reduce photosynthesis when water stress occurs, a mechanism that has been observed in this species during summer and early autumn, and does not show any summer quiescence (Liphschitz et al, 1984;Awada et al, 2003;Teobaldelli et al, 2004). It can therefore be considered as a drought-tolerant Mediterranean species that continues its growth, albeit reduced, during the dry season (Specht, 1981;de Lillis and Fontanella, 1992).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…From a physiological viewpoint, P. pinea is known to reduce photosynthesis when water stress occurs, a mechanism that has been observed in this species during summer and early autumn, and does not show any summer quiescence (Liphschitz et al, 1984;Awada et al, 2003;Teobaldelli et al, 2004). It can therefore be considered as a drought-tolerant Mediterranean species that continues its growth, albeit reduced, during the dry season (Specht, 1981;de Lillis and Fontanella, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…During the spring-summer period (March to September of the year of growth), the cambium activity takes place (Liphschitz et al, 1984). Then, the tree is highly dependent upon the amount of water stored in the soil for the construction of the ring (Campelo et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Liphschitz et al [37,38] showed that the cambial activity in P. pinea growing in semiarid sites in Israel starts in the middle of February or March and continues until November, without growth intermission in summer. The positive effect of February (t) temperature in earlywood and tree-ring width in the coastal area represented an early interruption of winter dormancy, which means an extension of the growing season and therefore wider tree rings.…”
Section: Discussionmentioning
confidence: 99%
“…This result suggests that growth in this species is less limited by warming induced drought stress during summer as compared to P. halepensis. This ability might be related to physiological-age interactions as P. pinea is characterised by high capacity to store water which minimizes water stress during summer, it reduces photosynthesis when water stress occurs and its high hydraulic conductivity enables the efficient use of underground waters (Liphschitz et al, 1984;Oliveras et al, 2003;Teobaldelli et al, 2004;Campelo et al, 2006). P. pinea trees in the study area are older than those of P. halepensis and such trees are less sensitive to drought conditions as opposed to the young trees (Carrer and Urbinati, 2004;de Luis et al, 2009;Olivar et al, 2012).…”
Section: Fig 3 Bootstrapped Correlation Coefficients For Climate-grmentioning
confidence: 99%